Novel deep eutectic solvent-based on lithium bis(fluorosulfonyl)imide and acetamide as high-performance electrolytes for 3.0 V asymmetric supercapacitor - Tuyen T.T. Truong (2022)
This paper illustrates the synthesis and physical characterization of a novel deep eutectic solvent consisting of lithium bis(fluorosulfonyl)imide (LiFSI) and acetamide (Ace) as a suitable electrolyte for supercapacitor. The formation of DES is finally pronounced in a liquid state at room temperature with a suitable molar ratio of LiFSI: Ace = 1:5(DES 1:5). Theoretical calculation confirmed DES structure formed through H-bond due to the strong interactions between –CO and –NH group of Ace precursors with Li+ and FSI− ions of lithium salt. As-synthesized DES exhibited high electrochemical stability (~5.0 V vs. Li+/Li), good thermal stability (~200 °C), and high ionic conductivity up to 1.97 mS·cm−1 at 30 °C. Different diluents such as ethylene carbonate (EC) and bis(2,2,2-trifluoromethyl) ether (BTFE) were used in a small amount to combine with pristine DES 1:5 so as to lower its viscosity and maintain its original features. DES-BTFE hybrid electrolytes mixture could significantly enhance the cycling performance at room temperature and improve cell safety at high temperatures. In EDLC capacitors, the hybrid electrolyte with DES-10%wt. BTFE displays capacitance of 23 F/g (1 A·g−1) corresponding to the energy density of 103.2 Wh·kg−1 at operating voltage 3.0 V and remains ~99.0% after 1000 cycles. In addition, our asymmetric capacitor device was successfully fabricated using MnO2 as a positive electrode and active carbon (AC) as a negative electrode in DES-based electrolytes. The asymmetric supercapacitor could be reversibly cycled in a wide potential window of 0–3.0 V and exhibits an energy density of 74.79 Wh·kg −1 with retention of 68.3% after 2000 cycles in DES (1:5) +10 %wt. BTFE.